Deuteronomy and Exhortation in Hebrews A Study in Narrative Re-presentation - Allen, David M. (Mohr Siebeck, 2008)
Das Deuteronomium und Ermahnung im Hebräerbrief. Eine Studie über erzählerische Repräsentation.
PublicationDate: 20080304
Keywords: Hebrews -- Deuteronomy -- Intertextuality -- Altes Testament -- Neues Testament -- Array